2022
DOI: 10.3390/cancers14236010
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery (CRS) and HIPEC for Advanced Ovarian Cancer with Peritoneal Metastases: Italian PSM Oncoteam Evidence and Study Purposes

Abstract: Ovarian cancer is the eighth most common neoplasm in women with a high mortality rate mainly due to a marked propensity for peritoneal spread directly at diagnosis, as well as tumor recurrence after radical surgical treatment. Treatments for peritoneal metastases have to be designed from a patient’s perspective and focus on meaningful measures of benefit. Hyperthermic intraperitoneal chemotherapy (HIPEC), a strategy combining maximal cytoreductive surgery with regional chemotherapy, has been proposed to treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 182 publications
0
3
0
Order By: Relevance
“…Research pertaining to QoL in women who underwent CRS with the inclusion of bevacizumab or hyperthermic intraperitoneal chemotherapy (HIPEC) demonstrated that the surgical intervention did not have a detrimental effect on their QoL. 19 Boer et al in their study highlighted that a higher QoL was seen in patients who had surgery with the use of the Plasma Jet device at 12 months postoperatively. The Plasma Jet is a thermal plasma energy device.…”
Section: Discussionmentioning
confidence: 99%
“…Research pertaining to QoL in women who underwent CRS with the inclusion of bevacizumab or hyperthermic intraperitoneal chemotherapy (HIPEC) demonstrated that the surgical intervention did not have a detrimental effect on their QoL. 19 Boer et al in their study highlighted that a higher QoL was seen in patients who had surgery with the use of the Plasma Jet device at 12 months postoperatively. The Plasma Jet is a thermal plasma energy device.…”
Section: Discussionmentioning
confidence: 99%
“…OC is the main cause of death in women with reproductive malignant tumors. The initial operation, with the goal of R0 resection and platinum‐based combination chemotherapy, is the standard treatment for OC 302,303 . Although the initial pharmacotherapy was encouraging, long‐term use of drugs resulted in drug resistance and was one of the main reasons for the discontinuation of cisplatin during chemotherapy 304–306 .…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 99%
“…The initial operation, with the goal of R0 resection and platinum-based combination chemotherapy, is the standard treatment for OC. 302,303 Although the initial pharmacotherapy was encouraging, long-term use of drugs resulted in drug resistance and was one of the main reasons for the discontinuation of cisplatin during chemotherapy. [304][305][306] Xie et al showed that the application of epigenetic approaches for the diagnosis, clinical treatment, and prognosis of OC is a promising area for future clinical research.…”
Section: Ovarian Cancer (Oc)mentioning
confidence: 99%